2017
DOI: 10.12681/eh.14007
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and Frequency of Coleoptera Found on Stored Cereals and Cereal Products in Central Greece

Abstract: Thirty Coleoptera taxa belonging to 14 families were found during samplings conducted in 4 different storage facilities at Farsala district, Central Greece, from January 1991 to February 1992. Among the most frequently found, Sitophilus oiyzae, S. granarius and Rhysopertha dominica were more numerous on grain. Tribolium confusum, T. castaneum and Cryptolestes ferrugineus on flour, while Oryzaephilus surinamensis and O. mercator showed no significant preference to any commodity. An analysis of the results was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
8
0
10
Order By: Relevance
“…Several studies have reported the presence of A. diaperinus in various storage facilities, e.g. warehouses, silos, mills etc., coexisting with other stored‐product insect species (Buchelos & Athanassiou , , ; Athanassiou & Buchelos , , ). In some cases, it has been found together with its relative species, the black fungus beetle, Alphitobius laevigatus (F.) (Coleoptera: Tenebrionidae) (Buchelos & Athanassiou ).…”
Section: Origins Distribution and Food Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the presence of A. diaperinus in various storage facilities, e.g. warehouses, silos, mills etc., coexisting with other stored‐product insect species (Buchelos & Athanassiou , , ; Athanassiou & Buchelos , , ). In some cases, it has been found together with its relative species, the black fungus beetle, Alphitobius laevigatus (F.) (Coleoptera: Tenebrionidae) (Buchelos & Athanassiou ).…”
Section: Origins Distribution and Food Preferencesmentioning
confidence: 99%
“…warehouses, silos, mills etc., coexisting with other stored‐product insect species (Buchelos & Athanassiou , , ; Athanassiou & Buchelos , , ). In some cases, it has been found together with its relative species, the black fungus beetle, Alphitobius laevigatus (F.) (Coleoptera: Tenebrionidae) (Buchelos & Athanassiou ). However, in contrast with poultry farms, where A. diaperinus is, together with flies, the major insect pest (Strother & Steelman ; Calibeo‐Hayes et al .…”
Section: Origins Distribution and Food Preferencesmentioning
confidence: 99%
“…In the case of stored product beetles, the infestation is manifested from several species at the same time (Madrid et al 1990, Buchelos and Athanassiou 1993, Subramanyam et al 1993. This fact influences negatively the effort of detecting the consequent presence of various species with different adult ratios in the same sampling unit.…”
Section: Introductionmentioning
confidence: 99%
“…Οι μέχρι τώρα αναφορές για κολεόπτερα στα προϊόντα που προαναφέρθηκαν με ταυτόχρονη επισήμανση των ευρεθέντων αριθμών ακμαίων των ειδών και των πληθυσμιακών διακυμάνσεων αφορούσαν περιορισμένο αριθμό αποθηκευτικών χώρων σε συγκεκριμένες περιοχές της χώρας. Ο Μπουχέλος (1981) αναφέρεται σε αλευρόμυλους στον Πειραιά, οι Buchelos και Athanassiou (1993a) σε τρεις αποθήκες και έναν αλευρόμυλο στην ευρύτερη περιοχή Φαρσάλων και οι Buchelos και Katopodis (1995) σε αποθηκευτικούς χώρους στην Λευκάδα. Επίσης οι Μπουχέλος και Αθανασίου (1995b) αναφερόμενοι σε χώρους της κεντρικής και νότιας Ελλάδας καταγράφουν ταυτόχρονα και την γεωγραφική εξάπλωση' ορισμένων ειδών στη χώρα.…”
Section: μέρος πρώτοunclassified
“…ΟΜπουχέλος (1985) αναφέρει ότι το Ρ. subdepressus βρίσκεται πιο συχνά σε αλευρόμυλους στην Ελλάδα, ενώ η κατάσταση αντιστρέφεται στις αποθήκες δημητριακών. Αντίστοιχα είναι και τα αποτελέσματα που παραθέτουν οι Bucheios καιAthanassiou (1993a), ενώ οι Μπουχέλος καιΑθανασίου (1995a) επιπροσθέτως σημειώνουν μεγαλύτερη εξάπλωση των Palorus spp. στις νοτιότερες περιοχές της χώρας.Τα δείγματα αχύρων είναι η κατηγορία προϊόντος που διαφέρει ποιοτικά από τις υπόλοιπες κατηγορίες, τόσο από άποψη πληθυσμών όσο και ειδών.Παρά τον μικρό αριθμό ακμαίων στα άχυρα, ο αριθμός των ευρεθέντων ειδών ήταν εντυπωσιακά μεγάλος.…”
unclassified